Inheritance Rights for Only Adopted Children Who Are Not Legally Competent Case Study of Tangerang Court Decision - Hidayatullah, Moh. Syarif (Sultan Agung Notary Law Review, 2023)
This research aims to determine and analyze the implementation of granting inheritance rights to single adopted children who are not legally competent based on the Judge's decision in Decision Number 640/Pdt.P/2021/PN Tng and to analyze the Judge's considerations in determining single adopted children who are not legally competent as individuals. in forgiveness. The approach method used in this research is the normative juridical method, namely the approach carried out by examining approaches to theories, concepts, and reviewing statutory regulations. The specifications of this research use analytical descriptive. The data used in this research is primary data which includes the 1945 Constitution; Law Number 2 of 2014; Law Number 35 of 2014; Government Regulation Number 54 of 2007; Civil Code, as well as secondary data containing books and other supporting documents. The data collection method in this research uses library study techniques. The data analysis method is qualitative and data is obtained descriptively. The research results show that the process of adopting a child must be carried out in accordance with certain procedures, conditions and must go through a court decision. An adopted child can inherit property from his parents through a testamentary or will. An adopted child who has limitations that make it difficult for him to take legal action or is not legally competent requires that he be appointed a guardian and designated as a person under guardianship.